POTENSI PENGEMBANGAN TANAMAN KOPI ARABIKA BERDASARKAN TINGKAT KESESUAIAN LAHAN DI DESA BULUKERTO, KECAMATAN BUMIAJI, KOTA BATU - Andre Susilo; Kurniawan Sigit Wicaksono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2023)
Bulukerto Village, Bumiaji District, Batu City is a village that is famous for its apple farming, but currently, the productivity of apples has decreased. The area of Arabica coffee plant development in Bulukerto Village is still not optimal. The purpose of this study was to evaluate the potential for developing arabica coffee plants based on the level of land suitability in Bulukerto Village, Bumiaji District, Batu City. The determination of sample points was based on the Land Map Unit and continued with soil sampling. The indicators observed in this study were water availability (wa) which consisted of annual rainfall and dry month length, altitude (h), slope (eh), root media (rc) which consisted of effective depth and soil texture, rocks in surface (s), drainage (oa), nutrient retention (nr) consisting of pH, organic C and cation exchange capacity, then available nutrients (n) consisting of total N, available P, and exchangeable K. Data analysis for actual land suitability used the method of comparing or matching data between actual land conditions and growing conditions for Arabica coffee plants. The results showed that the land condition in Bulukerto Village, Bumiaji District, Batu City, in general, has the potential for developing Arabica coffee, with potential land suitability indicating that an area of 438,77 ha of land has class S1 (suitable) and an area of 82,62 ha of land has class S2 (moderately suitable) with some limiting factors.